1986
DOI: 10.1152/jappl.1986.61.5.1634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of systemic venous pressure elevation on lymph flow and lung edema formation

Abstract: Pulmonary lymph drains into the thoracic duct and then into the systemic venous circulation. Since systemic venous pressure (SVP) must be overcome before pulmonary lymph can flow, variations in SVP may affect lymph flow rate and therefore the rate of fluid accumulation within the lung. The importance of this issue is evident when one considers the variety of clinical interventions that increase SVP and promote pulmonary edema formation, such as volume infusion, positive-pressure ventilation, and various vasoac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 0 publications
2
32
0
1
Order By: Relevance
“…5), at least not with the outflow pressures we applied. These results obtained with non-invasive techniques are similar to those obtained by Drake et al (1985) and Laine, Allen, Katz, Gabel & Drake (1986). They found that flow from cannulated lung lymphatics did not recover during 3 or 6 h periods of elevated outflow pressure in unanaesthetized sheep.…”
Section: Effect Of Outflow Venous Pressuresupporting
confidence: 87%
“…5), at least not with the outflow pressures we applied. These results obtained with non-invasive techniques are similar to those obtained by Drake et al (1985) and Laine, Allen, Katz, Gabel & Drake (1986). They found that flow from cannulated lung lymphatics did not recover during 3 or 6 h periods of elevated outflow pressure in unanaesthetized sheep.…”
Section: Effect Of Outflow Venous Pressuresupporting
confidence: 87%
“…Thus, the factors that may affect fluid clearance by the lymphatic system (Drake, Adcock, Scott & Gabel, 1982;Drake, Scott & Gabel, 1983;Laine, Allen, Katz, Gabel & Drake, 1986;Frostell, Blomqvist, Hedestierna, Halbig & Pieper, 1987a) appeared to be similar in all four groups.…”
Section: Effects Of Hhs Bolus Injectionmentioning
confidence: 87%
“…The effects of an increase in intrathoracic pressure on lymphatic flow were described a decade ago (51,52). In animal models, raising intrathoracic pressure reduced the lymphatic flow and impaired the clearance of lung edema (53)(54)(55). In our study, we found a positive correlation between the increase of esophageal pressure (i.e., the pleural pressure) and the edema formation rate after aIAP of 20 cm H 2 O (edema formation rate [ml/minute] ϭ 1.7 ϫ ⌬ esophageal pressure ϩ 7.0, r ϭ 0.83, p Ͻ 0.05, data not shown).…”
Section: Oleic Acid-injured Lungmentioning
confidence: 99%